STRATEGI BERTAHAN HIDUP PETANI DESA DENGAN MENJADI PEMULUNG DI KOTA (STUDI PADA PETANI DESA CIGORONDONG PANDEGLANG YANG MEMILIKI PEKERJAAN SEKUNDER SEBAGAI PEMULUNG DI KOMPLEK BMKG TANGERANG SELATAN) - Zaka Lawang, Robert Markus; Magfiroh, Hakiki (Jurnal Insani, 2019)
This study tried to explain one of the poor farmers groups in Cigorondong Village Pandeglang who made a survival strategy by diversifying their livelihoods. There are two factors behind it, driving factor from place of origin and the pull factor from the destination. After farmers in Cigorondong, Pandeglang, made a strategy to survive by diversifying their livelihood into scavengers in Komplek BMKG Tangerang Selatan, there were several economic and social conditions that had changed. In the economic aspect there is an increase in income. On the social aspect, the changes that occur are the existence of an organic solidarity attitude, namely solidarity that grows based on the division of labor as happens in urban communities. However, they do not abandon their rural social behavior such as obeying norms, mutual cooperation etc.